FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERSEPSI MASYARAKAT TERHADAP KEPATUHAN PROTOKOL COVID-19 PADA MASYARAKAT KOTA BAUBAU TAHUN 2020 - Sri Epon Hasti Dude; Fifi Nirmala; Irma Irma (FKM Universitas Halu Oleo, 2021)
The Perception Health Belief Model (HBM) explains that responses to comply with and respond to health health protocols can affect the increase in cases of COVID-19. Good preventive behavior will start from people's perceptions of these health behaviors. Good behavior can be an effort to prevent the transmission of COVID-19. Public compliance with health behavior is influenced by many factors, including knowledge, perceptions, emotions, motivation, and the environment. This study aims to determine the factors associated with compliance with the COVID-19 protocol in the people of Baubau City. This study used a cross sectional approach using simple random sampling technique, amounting to 420 people. Statistical test using the Chi-Square test. The results showed that 86 (20.5%) respondents with poor adherence found that there was a significant relationship with perceived vulnerability (p-value 0.000 <0.05), perceived resistance (p-value 0.000 <0.05) and guidance. act (p-value 0.000 <0.05), on the other hand there is no significant relationship with perceived severity (p-value 0.732> 0.05) and perceived benefits (p-value 0.701> 0.05). Conclusion: Individual knowledge about how risky a disease is can lead to taking preventive measures, other things that influence individuals not to carry out an action because of the many obstacles they feel and there are clues or motivations that make individuals take action. It was found that there was a significant relationship with perceived vulnerability (p-value 0.000 <0.05), perceived barrier (p-value 0.000 <0.05) and action instructions (p-value 0.000 <0.05), otherwise there was no a significant relationship with perceived severity (p-value 0.732> 0.05) and perceived benefits (p-value 0.701> 0.05). Suggestions for the community to maintain and improve themselves and be more productive by not forgetting the COVID-19 protocol, and for health institutions to further optimize the approach to the community and provide updated information so that people not only have better responses but also have good attitudes and behaviors in the prevention of COVID-19.